The Effect of Programmed Physical Exercise to Attention and Working Memory Score in Medical Students - Kevin Fachri Muhammad; Anam Ong; M. Nurhalim Shahib (Althea Medical Journal, 2015)
Background: Attention and working memory are two cognitive domain crucial for activities of daily living. Physical exercise increases the level of BDNF, IGF-1, and VEGF which contributes in attention and working memory processes.This study was conducted to analyze improvement of attention and working memoryafter programmed physical exercise of Pendidikan Dasar XXI Atlas Medical Pioneer (Pendas XXI AMP).Methods: An analytic observational study was conducted on 47 students from Faculty of Medicine, Universitas Padjadjaran during September-November 2012. Attention was assessed using digit span backward test, stroop test, visual search task, and trail making test. Working memory was assessed using digit span forward test and digit symbol test. Assessment was done on the 11th and 19th week of Pendas XXI AMP. Data distribution was tested first using a test of normality, and then analyzed using T-Dependent Test and Wilcoxon TestResults: Significant improvement was noted for attention in males based on working time for stroop test (26.50±5.66 to 22.03±3.78 seconds), working memory in males based on digit symbol test score (43.96±6.14 to 53.36±5.26 points), attention in females based on reaction time of visual search task for target absent (0.92±0.07 to 0.87±0.07 seconds), and working memory in females based on digit span forward score (5.42±1.30 to 6.63±1.07 points) and digit symbol test score (42.47±5.95 to 53.84±5.33 points.Conclusions: Exercise in Pendas XXI AMP improves attention and working memory for college students in Faculty of Medicine Universitas Padjadjaran. [AMJ.2015;2(1):291–97]